From above the story of aerial photography - McCabe, Eamonn 1948-; Padley, Gemma 1984- (Laurence King Publishing, 2019)
Since the birth of photography, photographers have been taking images of the earth from the air--with spectacular visual results. Celebrating over 150 years of these incredible images, this book tells the fascinating story of how these pictures were created, the technologies that have made them possible, and the photographers that have propelled image-taking to bold new heights. Taking advantage of the amazing sense of perspective that aerial photography offers, this incredible collection of images also offers a unique overview of the events, challenges, and changes of the past 150 years of human history
Keywords: Geschichte 1858-1918; Luftbild; Aerial photography / History; Aerial photography; History